2013
DOI: 10.1080/07929978.2014.961395
|View full text |Cite
|
Sign up to set email alerts
|

EMS, sodium azide and gamma rays induced meiotic anomalies in Delphinium malabaricum (Huth) Munz

Abstract: Meiotic cell division is a dynamic cellular process controlled by a large number of genes that act from premeiotic to postmeiotic mitosis. Mutation in these genes may cause anomalies that impair plant fertility. In this study, an attempt has therefore been made to understand the effects of ethyl methane sulfonate (EMS), sodium azide (SA) and gamma rays on the meiotic configuration of Delphinium malabaricum. The results demonstrated that the mutagens cause various types of cytological aberrations, such as univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…It is interesting to note that aberrations such as chromosome stickiness or clumping, disturbed pairing, and multivalents, orientation of chromosomes, disturbed spindle functioning lead to unequal clusters of chromosomes, aberrant microspores, abnormal cytokinesis, high pollen sterility can be induced through chemical mutagenesis. Similar types of aberrations have been observed in various plants raised from seeds treated with chemical mutagens (Gulfishan et al 2012, Kolar et al 2013.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is interesting to note that aberrations such as chromosome stickiness or clumping, disturbed pairing, and multivalents, orientation of chromosomes, disturbed spindle functioning lead to unequal clusters of chromosomes, aberrant microspores, abnormal cytokinesis, high pollen sterility can be induced through chemical mutagenesis. Similar types of aberrations have been observed in various plants raised from seeds treated with chemical mutagens (Gulfishan et al 2012, Kolar et al 2013.…”
Section: Discussionsupporting
confidence: 75%
“…Chromosome aberrations have been used as a measure of reproductive success in plants for many years and have been correlated with morphological and taxonomical changes, fertility sterility relationships, mutations, and other characteristics. The data on mitotic and meiotic analysis is of fundamental consideration for any given species in understanding the basic structure of the genetic complement; further, the mutagen-induced aberrations of the chromosome is the primary basis of genetic variation; therefore, investigations on the mechanism of chromosome breakage, type of aberrations and their genetic consequences form an integral part of most mutation studies (Kolar et al 2013). The studies also provide information regarding the response of various genotypes to a particular mutagen and give greater chances for the selection of desired characters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It usually induces base substitutions (mostly induced Guanine: Cytosine → Adanine: Thyamine transitions at the 2 nd codon position) and also produce DNA single strand breaks. Kolar et al [42] reported chromosomal aberrations by using sodium azide, however, reciprocal translocations and mitotic chromosomal aberrations have also been reported by sodium azide [43]. It has also been reported as an electron transport blocker, inhibitor of the respiratory chain and its immediate effect on the meristematic region is the dropping off its progression velocity in the cell cycle [44], its exact mechanism of action as a chemical mutagen is still not clear.…”
Section: Sodium Azide (Nan 2 ) Induced Mutagenesismentioning
confidence: 99%
“…Lagging of chromosomes may be either due to attachment to very weak spindle fibre or no attachment at all. Kolar et al [18] opined that due to the effect of mutagens, spindle fibres failed to carry the chromosome movement towards poles properly and resulting in the lagging chromosome appearing at anaphase. In addition, delayed terminalization, the stickiness of chromosome ends and failure of chromosomes segregation has led to laggard chromosome formation.…”
Section: Cytological Studiesmentioning
confidence: 99%